A Review on the Role of miR-1290 in Cell Proliferation, Apoptosis and Invasion - Ghafouri-Fard, Soudeh; Khoshbakht, Tayyebeh; Hussen, Bashdar Mahmud; Taheri, Mohammad; Samadian, Mohammad (Frontiers in Molecular Biosciences, 2021)
MicroRNAs (miRNAs) have been shown to affect expression of several genes contributing in important biological processes. miR-1290 a member of this family with crucial roles in the carcinogenesis. This miRNA is transcribed from MIR1290 gene on chromosome 1p36.13. This miRNA has interactions with a number of mRNA coding genes as well as non-coding RNAs SOCS4, GSK3, BCL2, CCNG2, KIF13B, INPP4B, hMSH2, KIF13B, NKD1, FOXA1, IGFBP3, CCAT1, FOXA1, NAT1, SMEK1, SCAI, ZNF667-AS1, ABLIM1, Circ_0000629 and CDC73. miR-1290 can also regulate activity of JAK/STAT3, PI3K/AKT, Wnt/β-catenin and NF-κB molecular pathways. Most evidence indicates the oncogenic roles of miR-1290, yet controversial evidence also exists. In the present review, we describe the results of in vitro, animal and human investigations about the impact of miR-1290 in the development of malignancies.